2009
DOI: 10.2118/09-03-42
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Oil Waterflooding: Effects of Flow Rate and Oil Viscosity

Abstract: Many countries in the world contain significant heavy oil deposits. In reservoirs with viscosity over several hundred mPa's, waterflooding is not expected to be successful due to the extremely high oil viscosity. However, in many smaller, thinner reservoirs, or reservoirs at the conclusion of cold production, thermal enhanced oil recovery methods will not be economic. Waterfloods are relatively inexpensive and easy to control; therefore, they will still often be employed in high viscosity heavy oil fields. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 18 publications
1
33
0
2
Order By: Relevance
“…There is only limited information published regarding the status of waterflooding after primary production (24,29) and the mechanisms of oil recovery at this stage are poorly understood. A separate study was conducted, comparing the response of waterflooding at different rates into unconsolidated sandpacks saturated with connate water and the same oil as was used in these cores (30) . The difference was that, in the previous study (30) , tests were conducted in gas-free systems.…”
Section: Waterflooding After Primary Recoverymentioning
confidence: 99%
“…There is only limited information published regarding the status of waterflooding after primary production (24,29) and the mechanisms of oil recovery at this stage are poorly understood. A separate study was conducted, comparing the response of waterflooding at different rates into unconsolidated sandpacks saturated with connate water and the same oil as was used in these cores (30) . The difference was that, in the previous study (30) , tests were conducted in gas-free systems.…”
Section: Waterflooding After Primary Recoverymentioning
confidence: 99%
“…However, because of the poor mobility ratio between heavy oil and water, water flooding does not have a satisfactory performance [4,5]. Due to this reason, even after water flooding, a significant amount of oil still remains in the reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, capillary bypassing takes place, causing oil to be surrounded by displacing fluid and trapped [9,10]. Capillary forces are typically neglected in heavy oil reservoirs; however, they are of importance [11]. Typically, heavy oil water flooding is avoided.…”
Section: Introductionmentioning
confidence: 99%
“…However, experience has shown that heavy oil reservoirs can provide around half of their cumulative output with a water cut of 90% and above, but the operator must be able to financially handle the large amounts of excess water produced for extended periods of time. In heavy oil reservoirs, viscosity differences are the primary cause of residual oil [11]. The viscosity ratio, defined as where μ Injected is the displacing fluid viscosity and μ Displaced is the displaced fluid viscosity, helps determine the in-reservoir flow pattern, which becomes fractal as M μ approaches 0 [12,13].…”
Section: Introductionmentioning
confidence: 99%